METANASI CO2 MENGGUNAKAN KATALIS NI/AL2O3 DENGAN VARIASI TEMPERATUR DAN ZN SEBAGAI PROMOTOR - Reza Aditya, Ahmad; Junaidi , Robert; Ramayanti, Cindi (DE FACTO : Journal Of International Multidisciplinary Science, 2023)
Carbon Dioxide (CO2) is one of the biggest contributors to the greenhouse effect. One way to reduce carbon dioxide in the atmosphere is to convert carbon dioxide and use it in chemicals, for example by hydrogenating CO2 into methane. The aim of this research is to produce methane gas from carbon dioxide using Ni/ Al2O3 and Zn catalysts with temperature variations and to determine the effect of variations in the addition of Zn and temperature on CO2 methanation. The method used is in situ. In this research, CO2 is used as a raw material with a Ni/Al2O3 catalyst of 8 grams and Zn will be adjusted to variations of 3.5, 4, 4.5, 5 and 5.5. To analyze the Methane (CH4) gas produced, it will be analyzed using a Multi Gas Detector Analyzer. The research results show that the highest value of methane gas produced in situ was obtained in sample 15 with a temperature variation of 60 0C and a Zn catalyst mass of 5.5 grams, namely 13.56%.